Establishment of Consumer Satisfaction by Aspects of Serviceability and Mix of Marketing at One Chicken Outlet Kasongan - Manti Apriyani; Bambang Sutejo (Universitas Darwan Ali, 2021)
The survey I conducted was meant to determine the consumer satisfaction formation by serviceability and mix of marketing aspects at One Chicken Outlet Kasongan. The samples used in this study were 75 respondents and the instrument in this study was a questionnaire using a Likert Scale. The data processing method uses multiple linear regressions. The results of research on serviceability show 0.691 a significant value with a 0.05 significant level, so which means that Ho is passed. Ha is declared not accepted, meaning that the serviceability variable contributes in the same direction and insignificant impact on consumer satisfaction. The survey results on the place variable showed a significant value of 0.026 with a 0.05 significant level so Ho was declared not accepted, and Ha was passed. This means that the place variable has a significant positive impact on consumer satisfaction. The results of the study on the price variable showed a 0.000 significant value with a 0.05 significant level. So Ho is declared not accepted and Ha is passed. This means that the price variable has a significant positive impact on consumer satisfaction. The results showed a 0.170 significant value with a 0.05 significant level so Ho was passed and Ha was declared not accepted. This means that the promotion variable has no significant positive impact on the consumer satisfaction variable.